Do Age and Linguistic Status Alter the Effect of Sound Source Diffuseness on Speech Recognition in Noise? - Avivi-Reich, Meital; Sran, Rupinder Kaur; Schneider, Bruce A. (Frontiers in Psychology, 2022)
One aspect of auditory scenes that has received very little attention is the level of diffuseness of sound sources. This aspect has increasing importance due to the growing use of amplification systems. When an auditory stimulus is amplified and presented over multiple, spatial-separated loudspeakers, the signal’s timbre is altered due to comb filtering. In a previous study, we examined how increasing the diffuseness of the sound sources might affect listeners’ ability to recognize speech presented in different types of background noise. Listeners performed similarly when both the target and the masker were presented via a similar number of loudspeakers. However, performance improved when the target was presented using a single speaker (compact) and the masker from three spatially separate speakers (diffuse) but worsened when the target was diffuse, and the masker was compact. In the current study, we extended our research to examine whether the effect of timbre changes with age and linguistic experience. Twenty-four older adults whose first language was English (Old-EFLs) and 24 younger adults whose second language was English (Young-ESLs) were asked to repeat nonsense sentences masked by either Noise, Babble, or Speech, and results were compared with those of the Young-EFLs previously tested. Participants were divided into two experimental groups: (1) A Compact-Target group where the target sentences were presented over a single loudspeaker, while the masker was either presented over three loudspeakers or over a single loudspeaker; (2) A Diffuse-Target group, where the target sentences were diffuse while the masker was either compact or diffuse. The results indicate that the Target Timbre has a negligible effect on thresholds when the timbre of the target matches the timbre of the masker in all three groups. When there is a timbre contrast between target and masker, thresholds are significantly lower when the target is compact than when it is diffuse for all three listening groups in a Noise background. However, while this difference is maintained for the Young and Old-EFLs when the masker is Babble or Speech, speech reception thresholds in the Young-ESL group tend to be equivalent for all four combinations of target and masker timbre.